Pseudomorphic transformation of amorphous calcium carbonate films follows spherulitic growth mechanisms and can give rise to crystal lattice tilting1. Issue 36 (28th September 2015) - Harris, Joe; Mey, I.; Hajir, M.; Mondeshki, M.; Wolf, Stephan E.
<x xml:space="preserve">Abstract</x> Tuning the pseudomorphic transformation of calcium carbonate allows for the generation of crystal lattice tilting similar to that found in calcareous biominerals.